Beyond marks: new tools to visualise student engagement via social networks - Joanne L. Badge; Neil F.W. Saunders; Alan J. Cann (Association for Learning Technology, 2012)
Evidence shows that engaged students perform better academically than disinterested students. Measurement of engagement with education is difficult and imprecise, especially in large student cohorts. Traditional measurements such as summary statistics derived from assessment are crude secondary measures of engagement at best and do not provide much support for educators to work with students and curate engagement during teaching periods. We have used academic-related student contributions to a public social network as a proxy for engagement. Statistical summaries and novel data visualisation tools provide subtle and powerful insights into online student peer networks. Analysis of data collected shows that network visualisation can be an important curation tool for educators interested in cultivating student engagement.